Business strategy and corporate responsibility: perception and practice in the oil industry and the role of non-governmental organisations - Ghalib, Asad K.; Agupusi, Patricia (Journal of Business Economics and Management, 2014)
This paper examines the strategies for the implementation of corporate social responsibility of various multinationals, with a particular focus on the oil industry. The role of non-governmental organisations towards inducing a more responsible behaviour is explored. By drawing on literature and reflecting on documented actions of various multinational corporations, particularly from the extractive sector, we find a commonalty that cuts across the board: a considerable disparity exists between policies, strategies and actions that these organisations display in the interest of their inherent, short-term economic gains. Such gains jeopardize interests of both internal and external stakeholders as well as the environment especially in the developing world. We argue that the disparity in implementation can be linked to weak structural institutions and lack of ethical standards in most developing countries.